AN ANALYSIS OF MARKETING COMMUNICATION STRATEGIES IN CATHOLIC EDUCATIONAL INSTITUTIONS IN RESPONSE TO DIGITAL DISRUPTIONS - Istyanto, Agatha Dwi Kartika Sari; Hamad, Ibnu; Nilamsari, Natalina (Moestopo International Review on Social, Humanities, and Sciences, 2025)
The rapid growth of technology and digital media has changed how Catholic schools interact and communicate. This study analyzes two schools—Santa Familia Elementary in Bangka Belitung and Santo Nikolaus High School in Manado—to explore their digital marketing strategies. It examines key aspects such as sales promotions, advertising, public relations, direct marketing, school activities, and the experiences of school community members. The study also identifies challenges these schools face in adapting to digital disruption. Using a constructivist paradigm and a qualitative phenomenological approach, the research incorporates document analysis, online interviews, and a literature review. Findings reveal that both schools acknowledge digital disruption and understand the importance of leveraging digital media to stay competitive. They are actively embracing digital transformation by focusing on social media engagement. Their communication strategies emphasize content creation, including visual, textual, and multimedia formats, aligned with six key aspects of integrated marketing communication. This approach helps them connect with their audiences and maintain adaptability in the evolving digital landscape.